2015
DOI: 10.1016/j.molp.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Genes Universally Control Key Agricultural Traits

Abstract: Circadian clocks are endogenous timers that enable plants to synchronize biological processes with daily and seasonal environmental conditions in order to allocate resources during the most beneficial times of day and year. The circadian clock regulates a number of central plant activities, including growth, development, and reproduction, primarily through controlling a substantial proportion of transcriptional activity and protein function. This review examines the roles that alleles of circadian clock genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
162
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(165 citation statements)
references
References 240 publications
(284 reference statements)
0
162
0
3
Order By: Relevance
“…Manipulating the central oscillator to enhance crop yield and traits of agronomic interest has been suggested for a long time (Bendix et al 2015). However, a key limitation in achieving this goal is that engineering the clockwork might lead to not only the expected response, but also unexpected interactions and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulating the central oscillator to enhance crop yield and traits of agronomic interest has been suggested for a long time (Bendix et al 2015). However, a key limitation in achieving this goal is that engineering the clockwork might lead to not only the expected response, but also unexpected interactions and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The processes controlled by the clock, as well as the molecular structure and several components of the core oscillator are conserved across different groups in the green lineage, including angiosperms and gymnosperms McClung 2013;Bendix et al 2015). Agricultural traits, such as flowering time and light responses, have been extensively studied and shown to be under circadian clock regulation in different species, including many crops (Bendix et al 2015).…”
Section: The Clock As the "Mastermind" Of Plant Lifementioning
confidence: 99%
“…RNA interference-mediated down-regulation of ZmMADS1 resulted in a delay of FTi in maize, while strong overexpression caused an early-flowering phenotype, indicating its role as a flowering activator. Taken together, we report that ZmMADS1 represents a positive FTi regulator that shares an evolutionarily conserved function with SOC1 and may now serve as an ideal stating point to study the integration and variation of FTi pathways also in maize.Flowering time (FTi) in crops is an important agronomical trait critical for harvesting date, biomass yield, crop rotation schemes, and terminal drought avoidance (Jung and Müller, 2009;Bendix et al, 2015). For flowering, the shoot apical meristem (SAM) has to change from vegetative to generative growth, a process called the floral transition.…”
mentioning
confidence: 99%
“…Flowering time (FTi) in crops is an important agronomical trait critical for harvesting date, biomass yield, crop rotation schemes, and terminal drought avoidance (Jung and Müller, 2009;Bendix et al, 2015). For flowering, the shoot apical meristem (SAM) has to change from vegetative to generative growth, a process called the floral transition.…”
mentioning
confidence: 99%
“…Pritchett et al (2015) reported that deletion of Grm3 disrupted sleep and activity and increased the sensitivity of the circadian system to light in mice supporting a role of this gene in photic entrainment and sleep regulation pathways. Modification of circadian rhythms and behavioral traits are considered forms of adaptation to faming or agronomical conditions and driven by major biological mechanisms that have been at the basis of the domestication processes of animal and plant species (Price, 1999;Kasahara et al, 2010;Bendix et al, 2015;Carneiro et al, 2014Carneiro et al, , 2015. Benhaïm et al (2013) reported behavioral differences between hatchery and wild-caught European sea bass.…”
Section: Selective Sweep Analysis In Cultivated European Sea Bassmentioning
confidence: 99%